6 years of bladder blog: Chances and benefits of a tool within the new media 6 Jahre Blasenblog: Chancen und Nutzen eines Tools in den neuen Medien - Wiedemann, Andreas; Hermanns, Udo; Naumann, Gert; Heppner, Hans Jürgen (Aktuelle Urologie, 2022)
Introduction ?Web-based information about urinary incontinence is rather rare, especially including features of a blog with periodically published teasers, small informative articles for patients. The contemporary blog the bladder is operated by Dr. Pfleger, Bamberg and attended by Prof. Dr. A. Wiedemann and Dr. G. Naumann as consulting experts. Acceptance and status of the bladder blog should be re-assessed. Methods ?6 years after the start of the project and 2 years after the relaunch of the underlying homepage the ranking of the blog in web-based keyword-searches was analyzed. Included questions, the blog-teasers and their effect in the ranking in Google results were evaluated with Google Analytics and other analysis tools with the items position (average position in Google results of all requests leading to the bladder blog), impression (frequency of mentioning the blog in Google results) and the click-through rate (pro-active visits of the homepage after being shown in Google in relation to the impressions).November 2018 served as the reference month. Results ?38 keywords that were really entered by users and reached at least 20 clicks lead to a number 1 ranking in Google results, further 60 keywords lead to a result within the first 10 notifications in Google. These resulted in a high click-through-rate - the real view of the blog homepage after being simply indicated by Google. The website had a total of 30,669 pageviews in November 2018.?The highest amount of clicks and impressions was recorded by the blog-article suprapubic or transurethral 1344 clicks und 21.357 impressions. In total, 164 questions within the blog were collected. These dealt predominantly with the topics urinary incontinence and overactive bladder and were predominantly posed by females (92 female, 38 male, 34 not evaluable by considering the nickname). 33 questions led to an inquiry-response circle containing up to 7 steps. The questions often showed a severe and complicated disease (e.?g. complete urinary loss 4 weeks after hysterectomy which should be awaited) or an incomprehensible lack of diagnostic tools ( my doctor is convinced to deal with a therapy resistant overactive bladder after several pharmaceutic attempts only by anamnestic information and urine analysis). Conclusion ?The bladder blog is a more and more intensively used, low-threshold information tool predominantly used by females around the topic urinary incontinence. Regularly published blog-articles succeed in highly relevant results in Google searches. The incoming questions often show a severe and complicated disease and sometimes?-?as analyzable in the questions - a lack of expertise of the practitioners.
CRIS-Team Scopus Importer:2022-09-26
Keywords: blog; new media; urinary bladder; urinary incontinence